Dependence analysis of ethanol, suga, oil, BRL/USD exchange rate and Bovespa: a vine copula approach - Anderson Gomes Resende; Osvaldo Candido (Economia Aplicada, 2015)
The aim of this study is to assess the dependence relationship of the sugarcane sector (represented by Ethanol and Sugar), Oil, BRL/USD Exchange Rate and Brazilian stock market (represented by the BOVESPA – Bolsa de Valores de São Paulo – Index). Our methodology is based on paircopulas constructions, in which tree specification are compared: Regular Vine, more general, and two particular cases, Canonical vine (C-vine) and Drawable vine (D-vine). Primary results are shown to be aligned with the existing literature but they can change significantly when conditional dependence is taken into account.